Factors associated with domestic violence against women in João Pessoa - Paraíba. - Jackeline Abílio de Souza; Ana Tereza de Medeiros; Ulisses Umbelino dos Anjos (Universidade de Brasília, 2016)
The aim of the present study was to investigate the factors associated with domestic violence against women in the city of João Pessoa, state of Paraíba, Brazil. For this purpose, we conducted a quantitative analytical study using logistic regression for the statistical analysis of the data. The study was conducted in the Police Station Specialized in Assistance to Women in João Pessoa, using a sample of 291 women older than 18 years of age, of which 206 had experienced domestic violence and 85 had not experienced domestic violence within one year of enrollment. The subjects were selected between April and August 2012 via convenience sampling. The variables related to personal, social, and economic characteristics were identified using a questionnaire and were used to construct the final probabilistic model. The results indicated that previous episodes of domestic violence against women involved an approximately five-fold increase in the likelihood of new episodes of violence. In addition, being retired or a pensioner involved an approximately nine-fold decrease in the chance of violence against women. With respect to men, an income lower than 2.5 times the minimum wage and a history of family violence involved a two-fold increase in the chance of abuse against the partner. The chance of aggression involved an approximately two-fold decrease in cases in which men were married. These findings indicate that domestic violence is a complex phenomenon and that its occurrence is associated with personal, social, economic, and cultural factors.